Meningkatkan Kemampuan Komunikasi Matematis Siswa SMA Melalui Penerapan Strategi Pembelajaran Relating, Experiencing, Applying, Cooperating, And Transferring - Nadhirah Nur Afifah; Puji Budilestari; Iwan Gunawan (Fakultas Keguruan dan Ilmu Pendidikan Universitas Langlangbuana, 2017)
Mathematics is one of the main subjects taught at every level of education. Mathematical communication skills are needed by students in understanding mathematics. But students' mathematical communication skills were still low. This is because teachers rarely train students' communication skills during the learning process. The purpose of this study was to determine the increase in mathematical communication skills of high school students through the implementation of REACT learning strategies. The method of this research is quasi-experimental research. Based on the results of data analysis, it was concluded that there was a better increase in students' mathematical communication skills both in writing and verbally which obtained REACT learning strategies than students who received conventional learning models. Thus REACT learning strategies can be used as an alternative for teachers in implementing their learning to improve students' mathematical communication skills.